2023
DOI: 10.54555/ccjls.7115.73896
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Competence, Moral Neutralization, and Cognitive Impulsivity in Relation to Future Delinquency: Understanding the Socialization Process

Abstract: The purpose of this study was to ascertain whether perception preceded belief when it came to predicting delinquency. Perceived parental competence served as the first stage of a socialization process designed to reduce delinquency. The second stage of this process entailed obstructing antisocial belief in the form of moral neutralization or cognitive impulsivity. We hypothesized that moral neutralization and cognitive impulsivity would mediate the relationship between perceived parental competence and delinqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Either there were an insufficient number of data waves to evaluate all four variables simultaneously, or a reasonable measure of one or more key variables was unavailable. Hence, the present study disclosed that a social context variable (parental support) preceded an internal perceptual variable (perceived parental support competence), whereas previous studies have shown that perception precedes belief (Walters et al, 2022) and affect precedes cognition (Walters, 2020a). Thus, while all of the relations proposed in the three rules ("affect before cognition," "perception before belief," "social context before affect/perception") have been verified, the full four-variable model has yet to be tested.…”
Section: Theoretical Implicationscontrasting
confidence: 79%
See 4 more Smart Citations
“…Either there were an insufficient number of data waves to evaluate all four variables simultaneously, or a reasonable measure of one or more key variables was unavailable. Hence, the present study disclosed that a social context variable (parental support) preceded an internal perceptual variable (perceived parental support competence), whereas previous studies have shown that perception precedes belief (Walters et al, 2022) and affect precedes cognition (Walters, 2020a). Thus, while all of the relations proposed in the three rules ("affect before cognition," "perception before belief," "social context before affect/perception") have been verified, the full four-variable model has yet to be tested.…”
Section: Theoretical Implicationscontrasting
confidence: 79%
“…Although previous research has uncovered support for the "affect before cognition" (Walters, 2020a) and "perception before belief" (Walters et al, 2022) rules, the current study sought to demonstrate that social context precedes perception and not vice versa. This provides preliminary evidence of an internalization process, consistent with social cognitive theory, that could be important to both development and learning.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations